2015
DOI: 10.1002/adhm.201500004
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Hierarchical Nano‐ and Micro‐Fabrication Technologies for Musculoskeletal Tissue Engineering

Abstract: Cells within a tissue are able to perceive, interpret and respond to the biophysical, biomechanical, and biochemical properties of the 3D extracellular matrix environment in which they reside. Such stimuli regulate cell adhesion, metabolic state, proliferation, migration, fate and lineage commitment, and ultimately, tissue morphogenesis and function. Current scaffold fabrication strategies in musculoskeletal tissue engineering seek to mimic the sophistication and comprehensiveness of nature to develop hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 196 publications
(189 reference statements)
0
30
0
Order By: Relevance
“…101 Among the physical decellularization methods, freezedrying is also mentioned. 63,91,102,103 Freeze-drying is undoubtedly a recognized and effective method for long-term storage of biological materials, 63,91,[104][105][106] but in terms of the effectiveness of removing cells from tissues and organs, issues similar like with cyclic freezing and thawing can arise. The removal of defaulting cell membranes, nucleic acids, and other cellular organelles can level off at unsatisfactory levels.…”
Section: Physical Decellularization Methodsmentioning
confidence: 99%
“…101 Among the physical decellularization methods, freezedrying is also mentioned. 63,91,102,103 Freeze-drying is undoubtedly a recognized and effective method for long-term storage of biological materials, 63,91,[104][105][106] but in terms of the effectiveness of removing cells from tissues and organs, issues similar like with cyclic freezing and thawing can arise. The removal of defaulting cell membranes, nucleic acids, and other cellular organelles can level off at unsatisfactory levels.…”
Section: Physical Decellularization Methodsmentioning
confidence: 99%
“…However, bioactive scaffolds with poorly defined degradation products require significant effort to establish safety, substantially increasing time and cost associated with preclinical and clinical assessment ( Webber et al, 2015 ; Ho-Shui-Ling et al, 2018 ). The design of a bioactive molecule(s) delivery system that can serve as a scaffold for cell attachment and matrix deposition, whilst promoting the active migration of cells, angiogenesis, and osteogenic cell differentiation, all in the right time and amount, appears as a mission impossible, unless more elegant, yet regulatory compliant systems, are developed ( Abbah et al, 2015 ; Thomas et al, 2016 ). It is also time to realize that a single molecule approach is unlikely to result in functional repair and regeneration ( Pugliese et al, 2018 ).…”
Section: Enhancing Bone Regeneration With Bioactive Materialsmentioning
confidence: 99%
“…37 For this reason, tissue engineering therapies have primarily focused in the development of hierarchical/anisotropic tissue facsimiles. [38][39][40] However, numerous studies have demonstrated that alignment alone is not sufficient and more biomimetic approaches should be employed for functional repair and regeneration. For example, a study suggested that electro-spun fiber diameter may be more important than fiber alignment in mesenchymal stem cell differentiation toward tendon/ligament lineage.…”
Section: Tendon and Ligament Mechanical Stimulationmentioning
confidence: 99%